Integrasi Model Inventori EOQ dan Time Series Forecasting Untuk Sistem Inventori Optimal - Britania, Rizka; Tjolleng, Amir; Ardiana Putri, Salma (Jurnal Visionida, 2024)
This research aims to evaluate the existing inventory system and determine the optimal inventory system for the future at PT XYZ. The methods used are Economic Order Quantity (EOQ) integrated with time series forecasting. The selection of products studied is based on inbound and outbound volumes in the warehouse. The application of the EOQ method to the five study products resulted in an optimal order quantity for the existing conditions of 925 drums, 737 drums, 612 drums, 705 drums, and 729 drums for products A, B, C, D, and E. There is a potential saving in total inventory costs of 24% generated by the EOQ model compared to the current inventory system in the company. Historical demand data shows a seasonal stationary pattern. Forecast for the coming year was conducted and used in calculating the optimal order quantity for the coming year, which are 775 drums, 891 drums, 611 drums, and 728 drums for products A, B, C, and E. This research can enrich the literature related to EOQ and provide input for companies regarding the potential savings that can be made, and information on inventory system needs for the future.    ABSTRAK Penelitian ini bertujuan mengevaluasi sistem inventori eksisting dan menentukan sistem inventori optimal untuk masa mendatang pada PT XYZ. Metode yang digunakan adalah Economic Order Quantity (EOQ) yang diintegrasikan dengan time series forecasting. Pemilihan produk yang dikaji didasarkan pada volume inbound dan outbound di gudang. Penerapan metode EOQ pada lima produk kajian memberikan hasil kuantitas pemesanan optimal untuk kondisi eksisting sejumlah 925 drum, 737 drum, 612 drum, 705 drum, dan 729 drum untuk produk A, B, C, D, dan E. Terdapat potensi penghematan total ongkos inventori sebesar 24% yang dihasilkan model EOQ dibandingkan dengan sistem inventori yang saat ini berlangsung di perusahaan. Data historis demand menunjukkan adanya pola seasonal stationer. Forecast untuk satu tahun mendatang dilakukan dan digunakan dalam menghitung kuantitas order optimal untuk tahun mendatang, yaitu sebesar 775 drum, 891 drum, 611 drum, dan 728 drum untuk produk A, B, C, dan E. Penelitian ini dapat memperkaya literatur terkait EOQ, dan memberikan masukan bagi perusahaan terkait potensi penghematan yang dapat dilakukan, dan informasi kebutuhan sistem inventori untuk masa mendatang.